Students with high abilities or giftedness: developments in the Synopsis and Microdata indexes in the Southeast Region of Brazil (Research, Society and Development, 2021)
High skills or giftedness (AHSD) belongs to the Special Education public and the students have right to specialized educational service, guaranteed in the Brazilian law. In this perspective, they are registered by the schools, and these records are stored, analyzed, and published by the Statistical Synopsis and Microdata. The research problem starts from the data of the Statistical Synopsis and Microdata of the Southeast Region of Brazil, in the years 2018 and 2019, both made available by the National Institute of Educational Studies and Research Anísio Teixeira (INEP), both made available by the Ministry of Education. The Brazilian Southeast Region is composed of four states: Espirito Santo, Minas Gerais, Rio de Janeiro, and São Paulo. Therefore, the objective was to investigate and analyze the enrollment rates of students with AHSD from the Statistical Synopsis and Microdata of the Southeast Region of Brazil in the years 2018 and 2019. The method used was qualitative and quantitative Documentary Research. Data collection was through the searches in the Statistical Synopsis and Microdata and analyzed in seven listed variables, in which the cross table and frequency were applied. The results obtained indicated a difference in the data from the Statistical Synopsis compared to the Microdata, because in the years 2018 and 2019 the Statistical Synopsis showed an increase of 486,42% of students with AHSD, and in the Microdata there was a growth of 387,22% in the same period. It is concluded that Microdata requires more transparency of access and exploration of data.